Production complementarity and information transmission across industries - Lee, Charles M.C.; Shi, Terrence Tianshuo; Sun, Stephen Teng; Zhang, Ran (Journal of Financial Economics, 2024)
Economic theory suggests that production complementarity is an important driver of sectoral co-movements and business cycle fluctuations. We operationalize this concept using a measure of production complementarity proximity (COMPL) between any two companies. We show firms from different industries but are closely aligned in COMPL exhibit strong co-movement in their operating, investing, and financing activities, as well as quarterly earnings revisions and monthly returns. We further document a lead-lag effect in their returns, such that a long-short strategy based on recent COMPL peer returns yields a monthly 6-factor alpha of 122 basis points. This inter-industry momentum spillover effect is not explained by other network-based mechanisms, such as shared analyst coverage. We conclude information transmission takes place along complementarity networks, but stock prices do not update instantaneously.